Association between “cluster of differentiation 36 (CD36)” and adipose tissue lipolysis during exercise training: a systematic review - El Ouali, El Mokhtar; Bosquet, Laurent; Elgharbaoui, Boutaina; Laziri, Fatiha; Laher, Ismail; Hackney, Anthony C.; Ibrahimi, Azeddine; Taib, Bouchra; El Harane, Sanae; Weiss, Katja; Knechtle, Beat; Mesfioui, Abdelhalem; et al. (Frontiers in Physiology, 2023)
Fatty acid translocase (FAT/CD36) is a transmembrane glycoprotein belonging to the scavenger class B receptor family and is encoded by the cluster of differentiation 36 (CD36) gene. This receptor has a high affinity for fatty acids and is involved in lipid metabolism. An abundance of FAT/CD36 during exercise occurs in mitochondria and solitary muscles. As such, we aimed to systematically review the evidence for the relationship FAT/CD36 and adipose tissue lipolysis during exercise training. Five electronic databases were selected for literature searches until June 2022: PubMed, Web of Science, Scopus, science direct, and Google Scholar. We combined the different synonyms and used the operators (“AND”, “OR”, “NOT”): (CD36 gene) OR (CD36 polymorphism) OR (cluster of differentiation 36) OR (FAT/CD36) OR (fatty acid translocase) OR (platelet glycoprotein IV) OR (platelet glycoprotein IIIb) AND (adipose tissue lipolysis) OR (fatty acids) OR (metabolism lipid) OR (adipocytes) AND (physical effort) OR (endurance exercise) OR (high-intensity training). All published cross-sectional, cohort, case-control, and randomized clinical trials investigating CD36 polymorphisms and adipose tissue lipolysis during exercise in subjects (elite and sub-elite athletes, non-athletes, sedentary individuals and diabetics), and using valid methods to measure FAT/CD36 expression and other biomarkers, were considered for inclusion in this review. We initially identified 476 publications according to the inclusion and exclusion criteria, and included 21 studies investigating FAT/CD36 and adipose tissue lipolysis during exercise in our systematic review after examination of titles, abstracts, full texts, and quality assessments using the PEDro scale. There were nine studies with male-only participants, three with female-only participants, and nine studies included both female and male participants. There were 859 participants in the 21 selected studies. Studies were classified as either low quality (n = 3), medium quality (n = 13), and high quality (n = 5). In general, the data suggests an association between FAT/CD36 and adipose tissue lipolysis during exercise training. Improvements in FAT/CD36 were reported during or after exercise in 6 studies, while there were no changes reported in FAT/CD36 in 4 studies. An association between fat oxidation and FAT/CD36 expression during exercise was reported in 7 studies. No agreement was reached in 5 studies on FAT/CD36 content after dietary changes and physical interventions. One study reported that FAT/CD36 protein expression in muscle was higher in women than in men, another reported that training decreased FAT/CD36 protein in insulin-resistant participants, while another study reported no differences in FAT/CD36 in young, trained individuals with type 2 diabetes. Our analysis shows an association between FAT/CD36 expression and exercise. Furthermore, an association between whole-body peak fat oxidation and FAT/CD36 expression during exercise training was demonstrated. Systematic Review Registration: [PROSPERO], identifier [CRD42022342455]